Effect of social deprivation on disease severity and outcome in patients with rheumatoid arthritis. Issue 7 (1st July 1997) - McEntegart, A; Morrison, E; Capell, H A; Duncan, M R; Porter, D; Madhok, R; Thomson, E A
Abstract : OBJECTIVE: Social deprivation is now recognised to have an important impact on morbidity and mortality. This study sought to ascertain the effect of deprivation, if any, on disease severity, functional disability, and outcome in rheumatoid patients in Glasgow. METHODS: 814 patients with rheumatoid arthritis (RA) were assessed for clinical, functional, and laboratory indices of disease activity. Deprivation categories for individual patients were determined using the Carstairs index. Five year follow up is available for 440 patients. RESULTS: The study population of RA patients live largely in the most deprived areas. Patients from deprived areas have significantly poorer function at outset and at five years as defined by the Health Assessment Questionnaire (HAQ) score. This is not attributable to differences in disease duration in patients from the most deprived regions or compliance with treatment. Furthermore, these patients do not achieve over five years the initial functional level of those living in the most advantaged localities. CONCLUSION: RA patients from deprived areas have poorer function, which is associated with greater need—medical, social, and paramedical. Strategies and resources for healthcare need to be adjusted according to this variation.